Screening sorghum varieties for salinity tolerance based on morpho-physiological and biochemical traits - DAFNI MAWAR TARIGAN; ANGGRIA LESTAMI; MAULIDA KHAIRIZA NAWAR; WAN ARFIANI BARUS; ASRITANARNI MUNAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Tarigan DM, Lestami A, Nawar MK, Barus WA, Munar A. 2025. Screening sorghum varieties for salinity tolerance based on morpho-physiological and biochemical traits. Biodiversitas 26: 5226-5237. The global food and energy crisis highlights the urgent need for alternative crops that can thrive on suboptimal land, including saline soils. Sorghum (Sorghum bicolor) is a promising candidate due to its wide varietal diversity and adaptive potential. Evaluating varietal responses under salinity is essential to identify the most tolerant and productive types. This study assessed the morphological, physiological, and biochemical responses of six sweet sorghum varieties (Suri 3, Super 1, Super 2, Soper 6, Soper 7, and Soper 9) under salinity stress with an electrical conductivity of 6.59 dS/m. A non-factorial Randomized Block Design (RBD) with three replications was employed. Plant performance was evaluated through key traits, including biomass, chlorophyll content, cuticle thickness, and seed biochemical composition. The results indicated that Suri 3 and Soper 6 demonstrated superior tolerance compared to the other varieties. These genotypes maintained higher dry weight, better chlorophyll retention, thicker cuticles, and enhanced protein content under saline conditions. Among the measured variables, dry weight, cuticle thickness, total chlorophyll, and protein concentration were the most influential in distinguishing varietal tolerance levels. The study highlights that a combination of morpho-physiological and biochemical traits can serve as reliable indicators for identifying salinity-tolerant sorghum genotypes. Such findings provide valuable guidance for sorghum breeding and improvement programs, particularly in the development of sustainable agriculture on saline-prone lands.